Does personalization really help in improving learning achievement? A meta-analysis - Tlili, Ahmed; Salha, Soheil; Wang, Huanhuan; Huang, Ronghuai; Rudolph, Jurgen; Weidong, Ren (Proceedings (IEEE International Conference on Advanced Learning Technologies), 2024)
Limited studies have quantitatively summarized the effect of personalized learning systems on learning achievement. To address this research gap, this study conducts a systematic review and a meta-analysis of personalized learning systems, where 19 studies (N = 3822) were included. The obtained results revealed that personalized learning has an overall medium positive effect (g = 0.45) on learning achievement. They further revealed that personalized learning systems based on Prompts & feedbacks and Diagnosis & suggestions do not significantly impact learning achievement. Finally, the results revealed that educational level, subject domain and continent might impact the effect of personalized learning systems on learning achievement. The findings of this study can contribute to the literature by explaining how the effect of personalized learning systems might vary depending on different moderating variables.